1999
DOI: 10.1021/jf990541b
|View full text |Cite
|
Sign up to set email alerts
|

Pseudovitamin B12 Is the Predominant Cobamide of an Algal Health Food, Spirulina Tablets

Abstract: The vitamin B(12) concentration of an algal health food, spirulina (Spirulina sp.) tablets, was determined by both Lactobacillus leichmannii ATCC 7830 microbiological and intrinsic factor chemiluminescence methods. The values determined with the microbiological method were approximately 6-9-fold greater in the spirulina tablets than the values determined with the chemiluminescence method. Although most of the vitamin B(12) determined with the microbiological method was derived from various vitamin B(12) substi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
103
1
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(111 citation statements)
references
References 18 publications
5
103
1
2
Order By: Relevance
“…contain substantial amounts of true B12 (17,18,22), but the other edible algae (kombu, duce or arame) shown in Tables 5 and 6 contain none or only traces of B12, especially, most of not be bioavailable in mammals (6)(7)(8). Our studies have demonstrated that most B12-compound found in spir ulina tablets is pseudo-B12 inactive for humans (19). IF involved in the intestinal absorption of B12 strictly rec ognizes the structure of the B12 molecule (30).…”
Section: Purification and Characterization Of B12 Compounds From Edibmentioning
confidence: 64%
See 2 more Smart Citations
“…contain substantial amounts of true B12 (17,18,22), but the other edible algae (kombu, duce or arame) shown in Tables 5 and 6 contain none or only traces of B12, especially, most of not be bioavailable in mammals (6)(7)(8). Our studies have demonstrated that most B12-compound found in spir ulina tablets is pseudo-B12 inactive for humans (19). IF involved in the intestinal absorption of B12 strictly rec ognizes the structure of the B12 molecule (30).…”
Section: Purification and Characterization Of B12 Compounds From Edibmentioning
confidence: 64%
“…Microalgae used for human health foods Spirulina (Spirulina sp., a blue-green alga) tablets also contain large amounts of B12 (7). The B12 concentration of spirulina tablets was determined by both Lactobacillus microbiological and IF-chemiluminescence methods (12,19). The values determined using the microbiolog ical method were about 9-fold greater than the values determined using the chemiluminescence method (Table 3).…”
Section: Purification and Characterization Of B12 Compounds From Edibmentioning
confidence: 95%
See 1 more Smart Citation
“…Vitamin B 12 : Liver homogenate, plasma or urine were added to 0.2 mmol/L acetate buffer (pH 4.8), and the vitamin B 12 was converted to cyanocobalamin by boiling with 0.0006% potassium cyanide at acidic pH ( 17 ). Cyanocobalamin was determined by the microbioassay method using Lactobacillus leichmanii , ATCC 7830 ( 17 ).…”
Section: Methodsmentioning
confidence: 99%
“…Urinary vitamin B 6 metabolite, 4-PIC was determined by HPLC (Gregory and Kirk, 1979). To measure urinary vitamin B 12 , urine samples were added to 0.2 mmol/l acetate buffer (pH 4.8), vitamin B 12 was converted to cyanocobalamin by boiling with 0.0006% potassium cyanide at acidic pH, and cyanocobalamin was determined by a microbioassay using Lactobacillus leichmanii ATCC 7830 (Watanabe et al, 1999). Urinary N 1 -methyl-2-pyridone-5-carboxamide, N 1 -methyl-4-pyridone-3-carboxamide (Shibata et al, 1988), and N 1 -methylnicotinamide (Shibata, 1987) were determined by the HPLC method, and the sum of these compounds was determined as nicotinamide metabolites.…”
Section: Urinalysismentioning
confidence: 99%